Histomorphological Structure of Single-Compartment Stomach (In the Example of Dogs and Cats) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Stomach is divided into 4 anatomical regions: cardia, fundus, body and pylorus. However, the stomach is divided into only 3 histological regions: cardia, fundus and pylorus. This is because the fundus and body are histologically the same, so both regions are called the fundus in histology. The cardia is a small area surrounding the opening of the esophagus that contains mucus-secreting glands.